1973
DOI: 10.1103/physrevd.8.698
|View full text |Cite
|
Sign up to set email alerts
|

Search for Magnetic Monopoles in Lunar Material Using an Electromagnetic Detector

Abstract: Our search for magnetic monopoles in lunar materials has been concluded with the exploration of an additional 11. 5 kg of material returned by the Apollo 11, 12, and 3.4 missions, using a modified version of our electromagnetic detector. Again, no magnetic monopole was detected. Combining these results with the results of our previous experiment, we set an upper limit of 1.7 x10 monopoles/g for the density of isolated monopoles in the lunar surface and improve our upper limits set for the monopole flux in cosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 6 publications
2
42
0
Order By: Relevance
“…Many years later my colleague in Oklahoma, George Kalbfleisch, asked me to join him in a new experiment to set limits on monopole masses based on Fermilab experiments [20,21]. His interest grew out of that of his mentor Luis Alvarez, who had set one of the best earlier limits on low-mass monopoles [22,23,24,25,26]. Thus, I believe I possess the bona fides to present this review.…”
Section: Introductionmentioning
confidence: 99%
“…Many years later my colleague in Oklahoma, George Kalbfleisch, asked me to join him in a new experiment to set limits on monopole masses based on Fermilab experiments [20,21]. His interest grew out of that of his mentor Luis Alvarez, who had set one of the best earlier limits on low-mass monopoles [22,23,24,25,26]. Thus, I believe I possess the bona fides to present this review.…”
Section: Introductionmentioning
confidence: 99%
“…These cross section limits are some 250 to 2500 times smaller and the mass limits are about 3 times larger than those of Bertani et al [13], and a significant improvement over those of Ross et al [17], as well. This appendix describes the basis of the functioning of our magnetic monopole dectector.…”
Section: Discussionmentioning
confidence: 64%
“…We have improved the cross-section and mass limits on directly produced magnetic monopoles over the best previous other limits of Bertani et al [13] and the lunar rock limits of Ross et al [17]. We have improved and extended our own prior limits from D0 samples [18] to those from CDF, with a consistent overall analysis, presented in this paper.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The sensitivity of our current measurements was determined during testing of the lunar samples. 3 We found that the error in 6Y , £, was £ "" 0.036 corresponding to errors in 6! of ± 70 pA.…”
Section: B the Current Changementioning
confidence: 99%